Good Environmental Governance dalam Pengelolaan Sampah di Kota Bandar Lampung - Gandhi Purnomo Nugroho; Rahayu Sulistiowati; Susana Indriyati Caturiani (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2023)
Rubbish is consequence from activity human . volume generated waste by man will always increase consequence from pattern life man like industry and house stairs. Amount generation garbage in the city of Bandar Lampung on The place Disposal Final (TPA) Bakung , Bandar Lampung. Recorded reach 1000 tons of waste per day . management rubbish rated important To use resolve accumulation garbage in Bandar Lampung City . Study this aim see implementation and barriers to good environmental governance in management garbage in Bandar Lampung City, with based on the theory put forward by belbase with 7 indicators namely 1. Rules of Law ; 2.Participation and Representation ; 3.Access to Information ; 4.Transparency and Accountability ; 5.Decentralization; 6. Institutions and Institution ; 7.Access to get justice . Results from study this could seen effort Service environment live in the city of Bandar Lampung in management rubbish based on principles of good environmental governance, out of 7 principles the found implementation rule the law still not yet held with good because still many the violation that occurred . then on implementation institution outside government found very role good because with volunteer help government in Thing management trash .